Psycho‐Social Factors Influencing Forest Conservation Intentions on the Agricultural Frontier. Issue 2 (3rd June 2013) - Mastrangelo, Matías E.; Gavin, Michael C.; Laterra, Pedro; Linklater, Wayne L.; Milfont, Taciano L.
Abstract Remnant forest fragments are critical to conserve biological diversity yet these are lost rapidly in areas under agricultural expansion. Conservation planning and policy require a deeper understanding of the psycho‐social factors influencing landholders' intentions towards conserving forest fragments. We surveyed 89 landholders in an agricultural frontier of the South American Gran Chaco and employed survey data to test three social psychological models: the Theory of Planned Behavior (TPB) and two modified versions of it, one integrated to the Norm Activation Theory (TPB‐NAT) and one including the effect of identity (TPB‐NAT‐Identity). The TPB was the most parsimonious model and explained a large variance of conservation intentions (41%). Social norms and attitudes had the largest direct influence on intentions across the three models, and identity had a significant role in shaping social norms and attitudes. Interventions aimed at building social capital within landholder networks provide the best hope for influencing pro‐conservation norms.